Perceived barriers for performing regular physical exercises in non-exercising individuals of the age group 18 to 25 years - Godbole, Sanika; Revadkar, Mayur (International Journal Of Community Medicine And Public Health, 2021)
Background: This study was aimed to find out barriers for performing regular physical exercises among non- exercising individuals of the age group 18 to 25 years under the category of physical, mental, college/ work related, environmental, social and others and to explore differences in perception of barriers with regards to gender and profession. Methods: A questionnaire consisting of 36 items was prepared based on review of literature to assess the barriers for physical exercises. A google form link was sent across through social media platforms like WhatsApp, Instagram along with a video prepared by the researcher. Demographic details were filled and online consent was taken from 427 respondents. The 201 respondents fitting to the inclusion criteria were recruited. (Mean age 21.6±0.13 years). Results: The 47.1% respondents were found to be “non-exercising”. College/ work related barrier was reported to be a leading barrier followed by mental barrier. The least common barrier reported was social barrier. Conclusions: The detailed analysis of barriers across genders and professions provides insight to health professionals-physical therapists, general physicians, psychologists about impact of barriers in this age group. Combined efforts of all health professionals, college/ work institution authorities shall play a major part in policy formulation at college/ work institutions to promote physical exercise participation as college/ work related barrier was the leading barrier.